A Contribution to the Problem of Researching Post-Roman Landscapes of Power on the Eastern Adriatic Coast. Case Study of Krk Island - Krleža, Palmira (Hortus Artium Medievalium, 2022)
Abstract This article is an overview of the sets of places of power in urban and suburban/rural contexts in the micro-area of the island of Krk, Croatia. First, the concept of places of power is terminologically and methodologically defined, mostly leaning on the definitions set in the essay collection “Topographies of Power in the Early Middle Ages” (2001) and placed in the Eastern Adriatic context. The established concept is then tested on the most important points in townscapes and landscapes of the island of Krk from the period of Antiquity to the early middle ages.